Creating a 3D neuronal-culture using alginate and collagen hydrogels optimal for neuronal survival and axon growth - Dalbayrak, Başak. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2021., 2021)
Alginate is a natural linear polymer that found in brown algae; also, it is biocompatible, biodegradable, and non-toxic. These properties make alginate favorable for biotechnological applications. In this thesis, 3D cell culture properties of extracted alginate from Cystoseira barbata was compared with commercially available alginic acid, sodium salt. Alginate hydrogels were used to create a three-dimensional neural cell culture to achieve survival and axonal outgrowth of two cell lines, mouse motor neuron (NSC-34) and neuroblastoma (SH-SY5Y). The cells were embedded with 1% (w/v) alginate hydrogels. Due to the lack of alginate receptors in these cells, cells in alginate tended to become together as aggregate. To decrease the clusters and increase cellular survival, the alginate was also mixed with collagen type I at a ratio of 2:1 alginate/collagen. In both cell lines, the alginate/collagen hydrogels did not significantly alter cell proliferation or axonal outgrowth when compared to only alginate hydrogels. In order to enhance axonal growth and survival in these hydrogels, NSC 34 cells were differentiated with nerve growth factor (NGF, 50 ng/mL) and fibroblast growth factor (FGF, 10 ng/mL), while SH-SY5Y cells were differentiated with serum withdrawal and retinoic acid (RA, 10 µM) treatment when seeding them in hydrogels. Survival of NSC-34 cells in hydrogels was improved with FGF and NGF treatment, and cellular clusters were decreased upon differentiation with FGF, and survival was found to increase also with NGF treatment. On the other hand, SH-SY5Y cells were not successfully differentiated within hydrogels upon serum withdrawal and retinoic acid treatment; the cells were observed to undergo stress after the addition of RA.|Keywords : Alginate, Hydrogel, Collagen, NGF, FGF, RA.
Keywords: Alginates -- Industrial applications.; Colloids.; Collagen.